A revision of the genus Olivancillaria (Mollusca: Olividae) from the southwestern Atlantic - Teso, Valeria; Pastorino, Guido (Zootaxa, 2011)
The genus Olivancillaria is revised and restricted to eight living species: O. deshayesiana, O. carcellesi, O. urceus, O. contortuplicata, O. orbignyi, O. teaguei, O. auricularia and O. vesica. The last two species were previously considered as subspecies. The name O. uretai is a junior synonym of O. orbignyi. The genus Olivancillaria is endemic to the southwestern Atlantic, ranging from Bahia state, Brazil ( 12°S) to Chubut province (42°37’S), Argentina, intertidal to 70 m depth. It is a clear representative of the Argentine Malacological province. Redescriptions and re-illustration of types were done for each species. Shell ultrastructure, radulae, penes, siphon papillae and egg capsules are described and illustrated by SEM images. A geometric morphometric analysis was carried out to confirm shell variation on size and shape among species. The geographic distribution of each species is provided based on field observations as well as on museum records.